Edukasi Kesehatan Pengaruh Gadget pada Remaja di SMA N 5 Kota Padang - Arinil Haq; Mega Utami Basra; Suci Maisyarah Nasution; Vivi Triana (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Excessive use of gadgets can have a negative impact on health and decrease adolescent interest in learning. The purpose of this community service is to increase the knowledge of teenagers about the bad effects of using gadgets in SMA N 5 Padang City. This community service was carried out at SMA N 5 Padang City with a target audience of 34 students. Community service activities consist of health education about the bad effects of gadgets and their prevention efforts. In addition, pre-test and post-test were also conducted to determine the level of knowledge of community service participants before and after health education was carried out. Statistical test results show that there is a significant difference between the level of knowledge before and after health education regarding the negative effects of gadgets and their prevention efforts in adolescents at SMA N 5 Kota Padang. It is hoped that with this activity, students can apply the prevention efforts that have been conveyed and invite their peers to participate in using gadgets wisely